Aplikasi Pupuk Kandang Ayam Terhadap Fase Pertumbuhan Tanaman Sorgum (Sorgum Bicolar L) - Siti Zahra Simatupang; Muhammad Nizar Hanadiah Nasution; Jumaria Nasution (Yayasan Perguruan Kampus, 2024)
Sorghum is a type of cereal crop that has great potential to be developed in Indonesia because it has good adaptability and is tolerant of drought, so sorghum has enormous potential to be developed as a source of nutrient-rich food. Sorghum contains protein (8-12%) which is higher than rice (6-10%), and its fat content (2-6%) is higher than rice (0.5-1.5%), also contains vitamin B, iron, phosphorus , potassium, and other micronutrients. To improve the quality and quantity of sorghum plants, fertilization is necessary. The current problem is that farmers using excessive chemical fertilization can reduce the quality and fertility of the soil, damage the soil ecosystem, and is not environmentally friendly.Efforts that can be made to improve and restore soil fertility are by organic fertilization. Fertilization is an activity of adding one or more nutrients to the soil when the level of availability is insufficient for the growth and development of a plant. This research aims to evaluate the application of chicken manure on sorghum growth at doses of 0 gr, 100 gr, 200 gr and 300 gr on the growth of stem height, panicle length and sorghum stem diameter. The design used was a non-factorial random design with 4 replications with 24 plants in one plot. The results obtained in this study were not significantly different.